CTV-to-PTV margin assessment for esophageal cancer radiotherapy based on an accumulated dose analysis. (August 2021) - Boekhoff, M.R.; Defize, I.L.; Borggreve, A.S.; van Hillegersberg, R.; Kotte, A.N.T.J.; Lagendijk, J.J.W.; van Lier, A.L.H.M.W.; Ruurda, J.P.; Takahashi, N.; Mook, S.; Meijer, G.J.
Highlights: The smallest clinical target volume (CTV) to planned target volume (PTV) margins that yielded full dosimetric coverage for esophageal cancer radiotherapy were assessed. Accumulated dose analysis revealed that CTV-to-PTV treatment margins of 8, 9 and 10 mm in posterior & right, anterior & cranial and left & caudal direction, respectively, are sufficient to account for interfraction tumor variations over the course of treatment when applying a daily online bone match. Even with these rather generous margins, outlying patients still do exist who may be underdosed and need special attention. Abstract: Purpose: This study aimed to assess the smallest clinical target volume (CTV) to planned target volume (PTV) margins for esophageal cancer radiotherapy using daily online registration to the bony anatomy that yield full dosimetric coverage over the course of treatment. Methods: 29 esophageal cancer patients underwent six T2-weighted MRI scans at weekly intervals. An online bone-match image-guided radiotherapy treatment of five fractions was simulated for each patient. Multiple conformal treatment plans with increasing margins around the CTV were created for each patient. Then, the dose was warped to obtain an accumulated dose per simulated fraction. Full target coverage by 95% of the prescribed dose was assessed as a function of margin expansion in six directions. If target coverage in a single direction was accomplished, then the respective margin remained fixed for the subsequent dose plans. Margins in uncovered directions were increased in a new dose plan until full target coverage was achieved. Results: The smallest set of CTV-to-PTV margins that yielded full dosimetric CTV coverage was 8 mm in posterior and right direction, 9 mm in anterior and cranial direction and 10 mm in left and caudal direction for 27 out of 29 patients. In two patients the curvature of the esophagus considerably changed between fractions, which required a 17 and 23 mm margin in right direction. Conclusion: Accumulated dose analysis revealed that CTV-to-PTV treatment margins of 8, 9 and 10 mm in posterior & right, anterior & cranial and left & caudal direction, respectively, are sufficient to account for interfraction tumor variations over the course of treatment when applying a daily online bone match. However, two patients with extreme esophageal interfraction motion were insufficiently covered with these margins and were identified as patients requiring replanning to achieve full target coverage.